Facial Artery Musculomucosal (FAMM) flap for nasal lining in reconstruction of large full thickness lateral nasal defects - Rahpeyma, Amin (Ann Med Surg (Lond), 2015)
Obviously, restoring the nasal lining is a great challenge in the reconstruction of nasal defects. Full thickness nasal defects usually require special flaps for reconstructing the nasal lining. Intranasal mucosal flaps, hinge over flaps, perinasal second flaps, folded or second forehead flaps and finally free flaps are examples that can be used for this purpose. Moreover, the case presented in this article expresses a new role for the superiorly based Facial Artery Musculomucosal (FAMM) flap in this topic. Furthermore, mucosal island variant of this flap is presented to reduce the tension on this flap while restoring the nasal lining in large full thickness nasal defect.